Transformation of Indonesian language learning: Integration of deep learning strategy with character education in the era of independent learning - Madeamin, Rosmini; Sahriani, Sahriani (International Journal of Nusantara Islam, 2025)
This study explores the integration of deep learning strategies with character education in the teaching of Bahasa Indonesia within the framework of the Merdeka (Independent) Curriculum. The primary objective is to examine how this pedagogical approach fosters meaningful, reflective, and context-driven learning experiences for students. Employing a qualitative descriptive method, the research was conducted at SMP Muhammadiyah 1 Makassar using participatory observation, in-depth interviews, and document analysis involving Bahasa Indonesia (Indonesian language) teachers and Grade VIII students. Findings reveal that the application of deep learning strategies actively engages students through text analysis, value-based discussions, and reflective writing, enhancing not only cognitive comprehension but also the internalization of core character values such as empathy, honesty, and responsibility. Teachers act as transformative facilitators who cultivate dialogic and humanistic learning environments, in alignment with the vision of the Merdeka Curriculum. Despite challenges such as limited instructional time and varying levels of student readiness, the approach has proven effective in shaping learners who are academically capable and morally grounded. In conclusion, the integration of deep learning and character education serves as a vital bridge between academic achievement and personal development. This research contributes both theoretically and practically to the development of adaptive, value-oriented instructional models relevant to 21st-century education. Moreover, it enriches the global discourse on holistic, values-based education and underscores the critical role of teachers as transformative agents in humanizing the learning process.